Distributive Property Calculator is a free online tool that displays the solutions for the given expression using the distributive property. BYJU’S online distributive property calculator tool makes the calculations faster and it displays the simplification of numbers in a fraction of seconds.

## How to Use the Distributive Property Calculator?

The procedure to use the distributive property calculator is as follows:

**Step 1:** Enter an expression of the form a (b+c) in the input field

**Step 2:** Now click the button “Submit” to get the simplified expression

**Step 3:** Finally, the simplification of the given expression will be displayed in a new window.

### Distributive Property in Maths

In Mathematics, the numbers should obey the characteristic property during the arithmetic operations. The different properties are associative property, commutative property, distributive property, inverse property, identity property and so on. The distributive property is the one which allows us to multiply the number by a group of numbers, which are added together. The distributive property is given by: **a(b+c) = ab + ac**

### Example

**Question:**

Simplify the given expression 4(2 + 8)

**Solution:**

Given expression: 4(2+ 8)

We know that the distributive property is given by:

a(b+c) = ab+ ac

Hence,

4(2 + 8) = 4(2) + 4(8)

=8+ 32

= 40

Therefore, 4 (2+8) is 40

3(x + 4)

3(x+4) = 3x+12

8 − 3(6 − 6𝑥)

8-3(6-6x) =8 -18+18x

=-10+18x

=18x-10

Can you please, distrubute 54 + 72?

Help me find this

18×4=(8×4)+(_ ×4)=

18×4=(8×4)+(10 ×4)= 72

I love this app it really helps

This is such a good website! Thank you for helping me do math!

What is the distributive property of 3(10n+9)

The distributive property of 3(10n+9) is 30n+27.

What is 7×4

7 x 4 = 28

simpilfy of [45-4{2(72÷9×5-24+8)-12}÷9+(8-5)

it is 32

x(8+9)=34

apply the distributive property to 4(9j+1+6j)

4 (9j + 1 + 6j)

= 36j + 4 + 24j

= 60j + 4

5(2d+4)=35

what is the distributive property 3(v+5)

6(2x-3)-8= -2

-11p + 6(1 – 11p) = 12(-7 – 10p) – 2p

Which of the following equations below illustrates Distributive Law?

7 × (3 + 16) = 7 × 3 × 7 × 16

5 + (9 + 0) = (5 + 9) + 0

5 × 9 = 9 × 5

25 × (5 + 9) = 25 × 5 + 25 × 9

7/8x+9/10-2x-3/5

1/2(-m-1)=8

y − 3(2y − 7) = 76

6(10+z+3)

6(-6 p – 6) + 2 = 146

i need to rewrite using distributive property 3(2x+5)

Using the Distributive Property,write the equivalent expressions of the following:

a(-x+y-z)=

-5(71+8m+9n)=

m(v-v)=

24x+18y+6z-12

3(n-7) =27

5(1+7k)

35+50

What is the distributive property of 4(2+m)=

264 x 15 using the distributive property.

What is the distributive property of the missing space?

81×20+97___=(81+97)×20

9x 4 1/3=

Multiply using distributive property;

(3a+4b)(a-2b)

3/2(5+6u)? Using distributive property

Can you help me with this answer pls -7x+-9+2+-8x

Can someone help me with 80 + 60w

Use the distributive property to write an expression that is equivalent to: 27x^2 -42x + 12

6(10+z+3)

6(10+z+3)=60+6z+18

= 6z+78

Can you please help me answer 7(2x + y) + 5(x+4y) using distributive property

7(2x + y) + 5(x+4y) = 14x+7y+5x+20y

= 19x+27y

5(___ + 15) = 5(21)

Let “x” be the unknown value

Thus, 5(x+15)= 5(21)

Using distributive property,

5x+75= 105

5x= 105-75

5x=30

x=30/5

x=6

Hence the unknown value in the equation is 6.

8(6s+y)

8(6s+y) = 48s+8y

Method: DISTRIBUTIVE

7y (2x + 8 )

7y (2x + 8 ) = 14xy+56y

3(t+2v)

3(t+2v)= 3t+6v

1. 4 (3x-5)

2. -2/3 (3x – 5)

4(3x-5)= 12x-20

-2/3 (3x – 5)= (10/3)-2x

Whats 7( 2 + 3z) Can you show your work too?

7( 2 + 3z) = 2(7) + 3z(7)

= 14 + 21z

3 × 15 = (3 × 12) + (3 × _)

Let the unknown value be “x”

45= 36+3x

45-36=3x

3x=9

x=3

Hence, the unknown value is 3.

4(5x-4y)

4(5x-4y) = 20x-16y

what is 6(3−12b)

and what are other ways and different answers

6(3−12b) = 18-72b

Different ways to represent 6(3−12b) are 2(9-36b), 3(6-24b), etc

im a bit confused on this problem

6(5 – 3x) – 5x = 99

6(5 – 3x) – 5x = 99

Using distributive property,

30-18x-5x=99

30-23x = 99

-23x= 99-30

-23x=69

x=-69/23

x=-3.

I need help with 11(3x + 5y)

11(3x + 5y) is equal to 33x+55y

(n-5)(-7)

(n-5)(-7)= 35-7n